Hematopoietic Stem cell transplantation and lentiviral vector‐based gene therapy for Krabbe's disease: Present convictions and future prospects. Issue 11 (November 2016) - Hu, Peirong; Li, Yedda; Nikolaishvili‐Feinberg, Nana; Scesa, Giuseppe; Bi, Yanmin; Pan, Dao; Moore, Dominic; Bongarzone, Ernesto R.; Sands, Mark S.; Miller, Ryan; Kafri, Tal
Abstract : Currently, presymtomatic hematopoietic stem and progenitor cell transplantation (HSPCT) is the only therapeutic modality that alleviates Krabbe's disease (KD)‐induced central nervous system damage. However, all HSPCT‐treated patients exhibit severe deterioration in peripheral nervous system function characterized by major motor and expressive language pathologies. We hypothesize that a combination of several mechanisms contribute to this phenomenon, including 1) nonoptimal conditioning protocols with consequent inefficient engraftment and biodistribution of donor‐derived cells and 2) insufficient uptake of donor cell‐secreted galactocerebrosidease (GALC) secondary to a naturally low expression level of the cation‐independent mannose 6‐phosphate‐receptor (CI‐MPR). We have characterized the effects of a busulfan (Bu) based conditioning regimen on the efficacy of HSPCT in prolonging twi mouse average life span. There was no correlation between the efficiency of bone marrow engraftment of donor cells and twi mouse average life span. HSPCT prolonged the average life span of twi mice, which directly correlated with the aggressiveness of the Bu‐mediated conditioning protocols. HSPC transduced with lentiviral vectors carrying the GALC cDNA under control of cell‐specific promoters were efficiently engrafted in twi mouse bone marrow. To facilitate HSPCT‐mediated correction of GALC deficiency in target cells expressing low levels of CI‐MPR, a novel GALC fusion protein including the ApoE1 receptor was developed. Efficient cellular uptake of the novel fusion protein was mediated by a mannose‐6‐phosphate‐independent mechanism. The novel findings described here elucidate some of the cellular mechanisms that impede the cure of KD patients by HSPCT and concomitantly open new directions to enhance the therapeutic efficacy of HSPCT protocols for KD. © 2016 The Authors. Journal of Neuroscience Research Published by Wiley Periodicals, Inc. Abstract : An L‐cycloserine‐mediated increase in insulin‐like growth factor 2 receptor expression in mouse CNS and an aggressive chemotherapy‐based conditioning regimen enhance the efficacy of bone marrow transplantation and gene therapy protocols for treating GALC deficiency in the Twitcher mouse model of Krabbe's disease.